Estudio de la práctica de los valores de paz en la cultura corporativa y espacios informativos de los medios de comunicación impresos de la ciudad de Loja en el año 2019 - Chuquimarca Carrión, Lida Karina (2021)
The present investigative work focused on the media of the city of Loja: "La Hora", "Crónica" and "Ecotel Press", with the main objective of studying the practice of the values of peace from their corporate culture, allowing to know how these values are disseminated from its informational spaces. To comply with the objectives, this research shows the relationship that exists between the peace values of the corporate culture of each printed medium, with the basic principles proposed by Unesco (Organización de las Naciones Unidas para la Educación, la Ciencia y la Cultura, in English, United Nations Educational, Scientific and Cultural Organization). All the news issued in 2019 from the daily "La Hora" and "Crónica" were analyzed, using a content analysis sheet, which has as sections: identification of the medium, information on the form of the news, nature of the sources, values and treatment of the news information, which made it possible to collect the news pieces. In the development of this research, it was possible to notice the scant dissemination of the values of peace within the informational spaces of the printed media, since, although there is a certain relationship between the values of peace and the principles established by Unesco, there is little information they have on the application of these values. It is necessary that all communication media have a corporate culture, in order to carry out certain situations in an orderly manner, where it is verified that the newspaper "Ecotel Press" does not have any element of corporate culture. Due to the little knowledge that the newspapers "La Hora" and "Crónica" have about the values of peace and as a contribution to the construction of a culture of peace, a guide on management and dissemination of a culture of peace in spaces is proposed. news media.